The Relationship between Religiosity and Academic Achievement in Students of Tehran University of Medical Sciences - Mansoureh Taghavinia; Mahmoud Motavassel (مجله ایرانی آموزش در علوم پزشکی, 2015)
Introduction: The relationship between religiosity and academic achievement of students can determine the distance between different aspects of religiosity and scientific development at university level and assist the authorities in planning to avoid a gap between the scientific and spiritual aspects of the universities. The purpose of this study was to investigate the relationship between religiosity in general and academic achievement of students in Tehran University of Medical Sciences. Methods: In this correlational study, a sample of 385 students (141 males and 244 females) in four educational levels (bachelors, Masters, MD and PhD) from among the students admitted at 2012 academic year were selected through stratified sampling )cluster and random). The data collection tool consisted of a demographic questionnaire and the 26-item Gluck-Stark`s questionnaire containing four aspects of beliefs, emotions, religious rituals, and consequences. The collected data were analyzed using descriptive statistics and Pearson correlation test. Results: Overall, no significant correlation was found between religiosity and academic achievement (p = 0.079). There was a significant positive correlation between religious rituals dimension and academic achievement (r = 0.115, p < 0.05). Conclusion: The findings of this study showed that the students were mostly weak in performing religious rituals and practice of religion. Therefore, attention has to be paid to strengthening the ritual aspect of religion. Moreover, as no positive correlation was found between religiosity and academic achievement in the four levels of education, it is important to identify other factors associated with religiosity.